PENGARUH IMPLEMENTASI TUGAS PANGGILAN GEREJA TERHADAP PETUMBUHAN IMAN WARGA JEMAAT ANTARDENOMINASI DI KOTA PEMATANGSIANTAR TAHUN 2020 - Elfri Darlin Sinaga (Jurnal Theologia Forum STFT Surya Nusantara, 2020)
The quality of growth and decline of the community's faith demands on the participations and involvements of all elements in society, including Churchâ€™s Christian community. The churchâ€™s Christian comunity is expected to play an active role in overcoming the problems of the nation by carrying out the church's calling Task, namely â€œkoinoniaâ€, â€œdiakoniaâ€ and â€œmarturiaâ€. The purpose of this study was to determine whether there is an effect of the implementation of Churchâ€™s Calling Task towards the growth of faith of the congregation and to find out how much the effect of the implementation of Churchâ€™s Calling Task (X) towards the growth of faith of the congregation among inter-denominational Churches in Pematangsiantar city (Y). Based on the research results, it was found that the growth of the congregation's faith (Y) can be influenced by the implementation of the Church's Calling Task (X). The method used in this research is descriptive analysis method, using a survey method, by distributing questionnaires to 40 respondents, as the representatives of 105 pastors of interdenominational Churches in Pematangsiantar city. The conclusions of the research results are as follows: (1) There is a strong and significant influence between the implementation of Churchâ€™s Calling Task (X) towards the Growth of faith of the Congregation (Y). Evidenced by the regression equation Y = 56.449 + 0.452 X2 with R = 0.424, t test = 2.888, and F count = 8.343 with P-value = 0.000 at Î±